Vulnerability as a Human Condition - Zagorac, Ivana (Array, 2014)
In this paper we will focus on the concept of vulnerability that sees vulnerability as an ontological condition of our humanity and/or an essential characteristic of the human condition. This view describes vulnerability as openness to being affected, both in the positive and negative way. A violent exploitation of one’s vulnerability can therefore be seen as an attack on humanity, while helping and protecting vulnerable individuals or groups is presented as an act of humanity. In general, this understanding of vulnerability is closely connected to the concepts of compassion and responsibility, outlining vulnerability within the field of traditional philosophical ethics. In the morally relevant sense, the term ‘vulnerable’ is used to note the susceptibility to being wronged or taken advantage of, i.e. the concern for someone’s lack of ability to safeguard her own interest. The relation between vulnerability and exploitation will be of our special interest here.